Silvio Guedes: a potência de um artista santanense - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2024)
This research aims to describe the story of the Santana artist Silvio Cleverton Guedes dos Santos, who over the years has worked tirelessly for the development of theater and culture in the municipality of Santana – AP. It is essential that we have this biography that represents his actions as an artist, and place him as a protagonist to inspire future research. We emphasize that the theme Silvio Guedes: The Power of a Santanense Artist emerged after reflections by the authors regarding the need to have a record around the history of an artist exclusively from the municipality of Santana, given that the city does not have a collection that present studies with the same context.
Keywords: Silvio Guedes; Teatro Santanense; Arte e cultura; CNPQ::LINGUISTICA, LETRAS E ARTES::ARTES::TEATRO; ODS 4 – Educação de qualidade; ODS 11 – Cidades e comunidades sustentáveis